The Possibilities of Color Duplex Scanning in the Assessment of Hemodynamic Eye Disorders in Children with Uveitis - L. A. Katargina; T. N. Kiseleva; E. V. Denisova; O. V. Novikova (Oftalʹmologiâ)
Purpose: to study the hemodynamic parameters in the eye’s vessels in children with endogenous uveitis, depending on the localization and degree and activity of the inflammatory process.Patients and methods: 67 children aged 6 to 18 years were examined. Of these, 19 people (35 eyes) were diagnosed with anterior uveitis, 20 (38) — peripheral, 8 (14) — posterior, 10 (20) — panuveitis. There were subgroups according to the degree of inflammation activity in each group. There were 10 healthy children (20 eyes) in the control group. The maximum systolic (Vsyst), final diastolic (Vdiast) blood flow rate and resistance index (RI) in the ocular artery (GA), central retinal artery (CAC), posterior short ciliary arteries (ZCCA), central retinal vein (CVS) and superior ocular vein (VGV) were detected with the method of the Color Duplex Scanning (CDR).Results. The maximum systolic and final diastolic blood flow rates in GA decrease, and in panuveitis, on the contrary, increase in anterior uveitis on the location of active inflamation. In panuveitis, the blood flow rate in the HBV also increases. In peripheral uveitis, there is a decrease in systolic and diastolic blood flow rates and an increase in the resistance index in CAC and WCC. With posterior uveitis, the blood flow in the HBV slows down and the RI in the CAC and WCC increases.Conclusion. In children with active uveitis, according to the CDR, hemodynamic changes in the vessels of the eye are observed, it depends on the localization of the inflammatory process. They have multidirectional nature. In most cases, a decrease in blood flow rate and an increase in RI are detected. The study of the eye’s hemodynamics can be an additional criterion for assessing the activity of inflammation and the effectiveness of therapy, as well as differential diagnosis of various localization of the uveitis.